Assessment of evapotranspiration loss of water from rice and wheat plants grown in sand and sandy soil in earthen pots under flood irrigation - Rahman, Md Khalilur (Dhaka University Journal of Biological Sciences, 2018)
Abstract not available Dhaka Univ. J. Biol. Sci. 27(2): 221-224, 2018 (July)